Advances in HIV and AIDS Control 2018
DOI: 10.5772/intechopen.77031
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Epitope-Based Immunogens in HIV-Vaccine Design

Abstract: One of the promising approaches for designing HIV vaccines is construction of synthetic polyepitope HIV-1 immunogen using a wide range of conservative T-and B-cell epitopes of the main virus antigens. In theory this approach helps cope with HIV-1 antigenic variability, focuses immune responses on protective determinants and enables to exclude from the vaccine compound adverse regions of viral proteins that can induce autoantibodies or antibodies enhancing infectivity of virus. The paper presents the experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 76 publications
1
11
0
Order By: Relevance
“…T-cell regions were associated with low viral load in vaccinated individuals (Mothe et al 2015). Our predicted Nef (63-75) CTL andPol (1362-1375) HTL epitopes overlapped with an extensive part of the identified Nef (WLEA-QEEEEVGFPVRPQV) and Pol (TKIQNFR-VYYRDSRDPLW) regions in ) in our study was present in TCI (T-cell immunogen) artificial polyepitope designed by Karpenko et al based on the Los Alamos HIV-1 Molecular Immunology Database and could induce both specific T-cell and antibody responses in vaccinated group (Karpenko et al 2018).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…T-cell regions were associated with low viral load in vaccinated individuals (Mothe et al 2015). Our predicted Nef (63-75) CTL andPol (1362-1375) HTL epitopes overlapped with an extensive part of the identified Nef (WLEA-QEEEEVGFPVRPQV) and Pol (TKIQNFR-VYYRDSRDPLW) regions in ) in our study was present in TCI (T-cell immunogen) artificial polyepitope designed by Karpenko et al based on the Los Alamos HIV-1 Molecular Immunology Database and could induce both specific T-cell and antibody responses in vaccinated group (Karpenko et al 2018).…”
Section: Discussionsupporting
confidence: 64%
“…So far, several HIV-1 therapeutic vaccine candidates were unsuccessful in clinical trials mainly due to inefficient delivery system or inadequate immunogen design (Fomsgaard 2015;Mothe et al 2019;Kardani et al 2020). One of the most promising approaches for developing HIV-1 therapeutic vaccine candidate is to design and construct artificial multiepitope (mosaic) immunogens using the selection of a wide range of highly conserved, immunostimulatory and protective T-cell epitopes from the main viral antigens that can induce potent immune responses against HIV-1 infection (Kulkarni et al 2014;Murakoshi et al 2015;Karpenko et al 2018). Therefore, bioinformatics tools can predict the highly immunogenic epitopes with high specificity in a short time for designing and developing a beneficial vaccine immunogen (Khairkhah et al 2018;Kardani et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The choice of PGS was due to the fact that we had previously successfully tested it for the delivery of DNA vaccines [21][22][23]39]. PGS was included in the candidate HIV-1 vaccine CombiHIVvac, which passed the first phase of clinical trials [40,41] which demonstrated the safety of the vaccine. The polyglucin envelop has also been shown to protect yeast dsRNA from degradation by serum nucleases [21].…”
Section: Discussionmentioning
confidence: 99%
“…A fixed-target experiment at the LHC would greatly extend its physics capabilities, offering many opportunities to study the nucleon/nuclear structure at high x, the properties of nuclear matter under extreme conditions in heavy-ion collisions, and the nucleon 3D/spin decomposition in terms of partonic degrees of freedom, which has been the topic of this talk. Extensive theoretical works have contributed to the development of a full physics program for a fixed-target experiment at the LHC, using both the multi-TeV proton and ion beams [31,19,32,13,33,20,34,35,36,23,37,38,39,40,41,31,42,43]. Several projection studies, based on the performances of ALICE and LHCb detectors in fixed-target mode [9,7,8,6,44,5,45], clearly show that unprecedented precise measurements are at reach, both on quark and gluon sensitive probes such as Drell-Yan, open heavy-flavour and quarkonium production.…”
Section: Discussionmentioning
confidence: 99%